Case Report: Remission of a patient with complex combination of autoimmune diseases by anti-CD19 CAR-T cell therapy - Liu, Xudong; Zhu, Wenxiang; Su, Nan; Ma, Yanyi; Wang, Fang; Xu, Jingyi; Zhang, Heyang; Luo, Xiaomeng; Zhao, Yuetong; Wang, Jianxun; Shi, Yuanyuan; Li, Yishuo; et al. (Frontiers in Immunology, 2025)
CAR−T cell therapy has been proven effective in various autoimmune diseases, with most studies utilizing lentiviral‐transduced CAR−T cells. In recent years, retroviral vector−transduced CAR−T cells—characterized by a high positivity rate, stable cell lines, and lower plasmid requirements—have attracted increasing attention. This article presents a complex case of a patient with SLE combined with APS and TBIRS. For four years following the diagnosis, the patient underwent conventional steroid therapy and immunotherapy, which yielded unsatisfactory and relapse−prone results. After receiving anti−CD19 CAR−T cells transduced with a retroviral vector, the patient experienced an excellent postoperative recovery without any infusion−related adverse reactions. Post−treatment, the patient’s creatinine, anti-dsDNA antibodies, albumin, and glycated hemoglobin levels returned to normal, eliminating the need for ongoing glucocorticoids or hypoglycemic agents. Although there are some available reports of CAR-T cells treating SLE, it is still very rare and significant for successfully treating such a complicated case, especially after proving the unavailability of traditional therapy. Furthermore, this is the first reported case of treating TBIRS syndrome with retroviral vector−transduced CAR−T therapy.